A recepção de Clausewitz no exército brasileiro: da guerra fria ao pós-guerra fria - Ferezin, Carla Cristina Wrbieta (2012)
Clausewitz is considered the main philosopher of war. Since the 19th century, his work was frequently read and cited, especially in the military environment. However, until now, no research has proposed investigating the reception of his work in Brazil. The central objective of this study is, more specifically, to analyze the reading of this author among members of the Brazilian Army. The specific objectives are: a) to investigate which Clausewitzian concepts are more cited in these readings; b) to consider the possible influence of the most important readings published abroad over these readings; c) to identify variations of comprehension about Clausewitz s conceptions during two periods: the Cold War and the post-Cold War; d) to examine the reception of Clausewitz in the Escola de Comando e Estado-Maior do Exército (Brazilian Army Command and General Staff School) ECEME. The corpus chosen was the geopolitics production that prevailed in the strategic thought of Cold War, as well as papers published in A Defesa Nacional, Revista do Exército Brasileiro e Revista das Ciências Militares Coleção Carlos de Meira Mattos, in the period post 1989. Curricula of the courses offered by ECEME were also examined. Through a bibliographical review and a documental analysis, it was verified that the Brazilian readings of Clausewitz are largely selective and marked by the historical context in which they were elaborated. Concerning the analysis of the ECEME s curricula, it was noticed that Clausewitz is a literature present in the Escola and read in the main course disciplines, Strategy and Military History.